The green platform molecule gamma-valerolactone – ecotoxicity, biodegradability, solvent properties, and potential applications. Issue 8 (18th March 2021) - Kerkel, Florian; Markiewicz, Marta; Stolte, Stefan; Müller, Eva; Kunz, Werner
Abstract : Solvent properties and (eco)toxicity of the renewable compound γ-valerolactone are investigated and its potential applications as a solvent as well as its toxicity towards the environment are outlined. Abstract : Since many decades, gamma-valerolactone (GVL) is known to be an excellent solvent, which, today, can be made of sustainable materials. Although numerous publications praise it as very green and versatile, GVL has never reached the level of a large-scale industrial product. Even relevant toxicity and biodegradability data are missing. In this paper, we present such data. Further, we make a detailed study, based on Hansen solubility parameters (HSP) and COSMO-RS calculations to identify harmful solvents that could be potentially replaced by GVL and to propose a variety of further applications of this substance. Toxicity tests with aquatic plants, bacteria, invertebrates, and a vertebrate cell line indicated a low acute toxicity of GVL towards aquatic organisms. Additionally, GVL was shown to be readily biodegradable, which further strengthens its potential as a "green" solvent. Accurate HSP of GVL were proposed and used in addition to COSMO-RS calculations to compare its solvent properties with the ones of classical, organic solvents. A similarity of GVL with several aprotic, highly dipolar solvents, such as the reprotoxic compounds N -methyl-2-pyrrolidone (NMP) and dimethylformamide (DMF), was found. Based on the results, GVL was concluded to be of interest as a green solvent in the manufacture of certain polymers or pharmaceuticals, as a cleaning agent in various paint and coating formulations, as well as a solubiliser in cosmetics, pharmaceuticals, or agrochemicals. Together with a very significant drop of its price, because of an intended large-scale production in Europe, the presented data should hopefully lead to the boost in applications that this green solvent deserves.